What was the message of Friedman - Forder, J (University of Oxford, 2016)
It is widely accepted that the importance of Friedman's Presidential Address to the American Economic Association lies in its criticism of policy based on the Phillips curve. It is argued that a reading of the text does not support such a view, and this and other considerations suggest that any such aim was far from Friedman's mind in 1968. His objective was the quite different one of making a case for policy 'rules' rather than discretion.